The female prostitute as «the Other» - Schouten, Maria Johanna Christina (2017)
The unconventional character of sex work often engendered images of female prostitutes as being anomalous persons. The professional activity then was believed to affect all aspects of life and personality of the sex worker. Inversely, a conviction has existed that only specific types of women, with certain physical and mental characteristics, will enter this trade. This notion of the female prostitute as The Other was particularly powerful in western thought at the end of the nineteenth century and the beginning of the twentieth century, and in the paper the ideas of that period about the “otherness” in its various layers will be explored. This period was also the zenith of imperialism, the domination of Other people and inherently the sexual encounter of occidental men with oriental and African women. The images of these “exotic” women and the practice of prostitution in a colonial context is an additional topic in this paper, to be related with the ideas in Europe about sex work.